The Theater Plays the Body. Replication of the Canon of Beauty among Young Actresses in the Theater - Dwojnych, Anna; Kuczkowska-Golińska, Katarzyna (Qualitative Sociology Review, 2018)
The article presents the results of our independent qualitative research conducted in Polish theater circles. In-depth interviews have been conducted with fourth-year female students of acting faculties from four state theater schools and with lecturers working at these faculties. The aim of the study was to answer the question whether the theater has currently become a place where bodily images are being standardized and beauty canons reproduced. The research material gathered allows for the formulation of the following conclusions: 1) studying at a theater school significantly impacts the perception of one’s own body, 2) there is a widespread belief among the students concerning the importance of the body (and the beauty thereof) in the profession of an actor, which results in subjecting the body to some regimes, often destructive ones, 3) the pressure to have a perfect body is so strongly internalized in the theater circles that it becomes imperceptible to those who yield under this pressure.